Biochemical characterization of three distinct polygalacturonases from Neosartorya fischeri P1. (1st December 2015) - Pan, Xia; Li, Ke; Ma, Rui; Shi, Pengjun; Huang, Huoqing; Yang, Peilong; Meng, Kun; Yao, Bin
Highlights: Three extracellular N. fischeri polygalacturonases were produced in P. pastoris . NfPG I showed higher specific activity (40, 123 U/mg) than other recombinant PGs. NfPG II showed better thermal adaptability at 65 °C than its counterparts. NfPG III is a typical acid enzyme with the lowest pH optimum of 3.5. Enzyme combinations showed better performance in juice processing and clarification. Abstract: Polygalacturonase is one of the most important industrial pectinases. To enrich the genetic resources and develop new enzyme candidates, three polygalacturonase genes ( Nfpg I – III ) of glycosyl hydrolase family 28 were cloned from Neosartorya fischeri P1 and functionally expressed in Pichia pastoris . The purified recombinant proteins exhibited some distinguished properties. In comparison with other counterparts, NfPG I showed the highest specific activity (40, 123 U/mg), NfPG II had the highest temperature optimum (65 °C), and the pH optimum of NfPG III was the lowest (3.5). The orders of their thermostability and resistance to chemicals tested were NfPG II > NfPG III > NfPG I and NfPG II > NfPG I > NfPG III, respectively. Combinations of these enzymes showed better performance than individuals in the processing and clarification of apple and strawberry juice. These results suggest that N. fischeri polygalacturonases have great application potentials in the food industry for juice production.